2007
DOI: 10.1007/s00228-007-0401-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and patterns of methylphenidate use in French children and adolescents

Abstract: Although there is a low prevalence of MPH use in France, this survey revealed a wide profile of users and heterogeneous use patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 24 publications
5
33
1
2
Order By: Relevance
“…Despite the persistent nature of ADHD symptoms and the demonstrated effect of current ADHD medications, treatment discontinuation is relatively common (16,25,26,(29)(30)(31)(32)(33). Our longitudinal cohort analysis confirmed this observation; only 42% of initial patients were still under ADHD drug treatment at the end of the study (after 3 years and 11 months).…”
Section: Rates Of Treatment Discontinuation From 2006 To 2009supporting
confidence: 88%
See 1 more Smart Citation
“…Despite the persistent nature of ADHD symptoms and the demonstrated effect of current ADHD medications, treatment discontinuation is relatively common (16,25,26,(29)(30)(31)(32)(33). Our longitudinal cohort analysis confirmed this observation; only 42% of initial patients were still under ADHD drug treatment at the end of the study (after 3 years and 11 months).…”
Section: Rates Of Treatment Discontinuation From 2006 To 2009supporting
confidence: 88%
“…It is well established that the prevalence of prescribing ADHD medications varies considerably between countries (21)(22)(23)(24).The observed prevalence in this study is lower than that reported in the USA (20,24) and in the Netherlands (25), but higher than in France (26) and in the UK (27). Several factors have been suggested to explain the geographic variation in ADHD medication use prevalence: psychopathology, nosology, clinical practice and guidelines, drug regulations, healthcare organization, and cultural factors (28).…”
Section: The Cross-sectional Prevalencecontrasting
confidence: 84%
“…, the Netherlands [10] , Spain [11] and France [12,13] . Since product availability of psychoactive medication has been described as one of the determinants of its abuse [3,14] and because prescription medications are becoming the most prevalent abused drugs in economically developed countries [15,16] , it is important to assess MPH use as prescribed and to monitor its potential abuse in a 'reallife' setting.…”
Section: Patterns Ofmentioning
confidence: 99%
“…Somente um artigo 2 faz essa referência. Pressupondo-se que o TDA/H seja de origem neurobiológica e de curso crônico, o esperado é que a medicação seja mantida por anos, mas o encontrado foi que em até 50% das pessoas ela não foi mantida por mais de 5 meses [9][10][11] , verificando-se baixos níveis de adesão. Isso leva a pensar que os médicos estão falhando no aspecto técnico (diagnóstico) ou na questão cultural (interlocução com a família).…”
Section: Discussionunclassified
“…Cox et al 10 sugeriram média de 4 prescrições/ano e que 13% tiveram somente uma receita. Knellwolf et al 11 mencionaram média global de 10,2 meses de uso para os iniciantes. O tempo de uso foi de curto prazo em 17%, cinco meses em 34% e 26 meses em 50%.…”
Section: Tempo De Usounclassified